PENGARUH KEPEMIMPINAN, PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT TUNAS CAHAYA MANDIRI WIDYATAMA MEDAN - Sitompul, Pandapotan; Sihombing, Watalina; Tinambunan, Anitha P.; Purba, Saut (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The purpose of this research is to determine and explain the influence of leadership, training and compensation on employee performance at PT Tunas Cahaya Mandiri Widyatama Medan. Data collection was carried out using a questionnaire. Before testing the hypothesis, the classical assumption test is first carried out. The analysis used multiple linear regression, hypothesis testing (F test and t test) and analysis of the coefficient of determination. From the results of data processing, a multiple linear regression equation is obtained where: Y= 1.106 + 0.319 X1 + 0.306X2 + 0.365X3 + ei. The results of this research show that the variables of leadership, training and compensation together (simultaneously) have a positive and significant effect on employee performance. Partially, it shows that leadership has a positive and significant effect on employee performance with a multiple regression coefficient value of 0.319 and a significant value of 0.036 <0.05. Training has a positive and significant effect on employee performance with a multiple regression coefficient value of 0.306 and a significant value of 0.045 <0.05. Compensation has a positive and significant effect on employee performance with a multiple regression coefficient value of 0.365 and a significant value of 0.040 <0.05. The results of this research also conclude that to improve employee performance, companies should pay more attention to leadership, training and compensation.